Detection of asynchronicity in the amplitude modulation domain - Kutzner, D.; Lemańska, J.; Sęk, A. P. (Archives of Acoustics, 2005)
A just noticeable time delay (JNTD) between the onset of a single sinusoidal amplitude modulation (AM) and a complex modulation applied to the same carrier was measured in this study. The carrier was a 4-kHz tone and the modulator was a five-component multitone complex. In the first experiment, four of five components had constant frequencies, i.e. 160, 170, 180, 190 Hz and they were turned on synchronously (synchronous components) in the middle of the carrier duration. The frequency of the fifth component (asynchronous one) varied from 10 to 150 Hz and it was turned on earlier than the synchronous ones. In the second experiment, the asynchronous component was situated in the centre of the synchronous components' spectrum; its frequency was constant and equal to 100 Hz. The spectral separation between the asynchronous component and the synchronous ones of the modulator varied. The results, i.e. the just noticeable time delay between the onset of a single sinusoidal amplitude modulation and a complex modulation (or asynchrony threshold), are analogous to those obtained in the audible frequency domain. They can be interpreted on the basis of the auditory system model containing a bank of modulation filters. It seems that two separate mechanisms are responsible for the JNTD between the onset of the single component modulation and the complex modulation. The first one results from an interaction between all the components of a modulator passing a single modulation filter tuned to the frequency of the asynchronous component. This sort of interaction (or masking) was most effective when the spectral separation between the asynchronous component and the synchronous ones was the smallest one. With an increase in this separation, a significant decrease in the asynchrony thresholds was observed. The second mechanism determining the obtained asynchrony thresholds is based on the uncertainty principle: modulation filters with good frequency selectivity, i.e. filters tuned to low modulation rates, are characterised by a poor time resolution. Thus, in the case of the lowest frequencies of the asynchronous component the subjects' performance would be relatively poor even when there was a significant spectral interval between this component and the synchronous ones. As in the audible frequency domain, the pattern of the asynchronicity thresholds was related to the modulation filter bandwidth. The obtained results suggest the bandwidth of the modulation filters whose Q factor should be close to 1 or less.